2013
DOI: 10.1097/shk.0b013e31829c361d
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine Pretreatment Improves Survival, Liver Function, and Hepatic Microcirculation After Polymicrobial Sepsis in Rat

Abstract: Dobutamine is recommended for the treatment of sepsis-related circulatory failure in international guidelines. Furthermore, dobutamine has been demonstrated to improve liver function and hepatic perfusion after experimental hemorrhagic shock. Yet, it is unknown whether dobutamine may also induce hepatoprotective effects in sepsis. This study was designed to investigate the effect of dobutamine on survival, hepatic function, and microcirculation after polymicrobial sepsis in rat. Under general anesthesia, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
2
11
1
Order By: Relevance
“…Anyway, these results are surprising, as previous studies demonstrated decreased liver function and increased hepatocyte damage in rats after 5 h of CLI sepsis (Fink et al, 2013). However, melatonin treatment did influence the expression levels of the UPR mediators PERK and CHOP in the liver of septic mice.…”
Section: Discussioncontrasting
confidence: 54%
“…Anyway, these results are surprising, as previous studies demonstrated decreased liver function and increased hepatocyte damage in rats after 5 h of CLI sepsis (Fink et al, 2013). However, melatonin treatment did influence the expression levels of the UPR mediators PERK and CHOP in the liver of septic mice.…”
Section: Discussioncontrasting
confidence: 54%
“…Furthermore, we found that intravenous dobutamine at a dose up to 10 µg/kg signi cantly improved the survival in septic rats with myocardial dysfunction. This nding dovetails well with other studies which demonstrated that DOB had improved the survival in patients with septic shock and animal models of sepsis [34,35]. We also found intravenous dobutamine at a dose of 10 µg/kg markedly increased serum IL-10 level in CLP rats.…”
Section: Discussionsupporting
confidence: 91%
“…Pretreatment with dobutamine improves survival rate, liver function and hepatic microcirculation in septic rats via β1-adrenoceptor activation, in addition to its circulatory mechanism. [59] Dexmedetomidine, a novel lipophilic imidazole derivative with a high affinity for α2-adrenoceptors, has a protective effect on liver injury during experimental sepsis. It attenuates central venous congestion, hepatic sinusoids congestion and dilation, and portal tract inflammation.…”
Section: Therapeutic Considerations For Sepsis-associated Liver Dysfumentioning
confidence: 99%